Diffusion kinetics and evolution of self-assembled nickel germanide nanorings on germanised Si (100). Issue 42 (8th April 2015) - Panda, D.; Dhar, A.; Ray, S. K.
Abstract : Self assembled binary nickel germanide nanorings are formed by annealing of a Ni/Ge/Si (100) film. Abstract : Self assembled binary nickel germanide nanorings are formed by annealing of a Ni/Ge/Si (100) film. Nickel germanide phase formation is confirmed by an X-ray diffraction (XRD) and X-ray photo electron spectroscopy (XPS) study. Rutherford backscattering spectrometry (RBS) measurement has been used to analyse germanide compositions and film thickness of the different annealed samples. Composition of the binary germanide phases from RBS simulation, agrees well with the XRD data. Atomic force microscopy (AFM) topography has been used to study nanoring evolution. Scanning electron microscopy (SEM) structures agree well with the AFM results. Nanoring formation mechanisms have also been explained with schematic structures. Nanostructures and lattice spacing of germanides have been studied from transmission electron microscopy (TEM) micrographs and selected area diffraction pattern (SAED) pattern.